Ethnicity and the surgical management of early invasive breast cancer in over 164 000 women in England - Gathani, T; Chiuri, K; Broggio, J; Reeves, G; Barnes, I (Oxford University Press, 2020)
Background: Limited information is available about patterns of surgical management of early breast cancer by ethnicity of women in England, and any potential inequalities in the treatment received for breast cancer.